The Legal Adaptation of Modern Administrative Contracts - Dogma, Abdulatef Hussein Qasem; Al-Maamari , Abdulwahab Abdullah (Dirasat: Shari’a and Law Sciences, 2020)
The management uses the decisions of the departments when it regulates and facilitates the public facilities which are individually taken by the management without resorting to the second party. However, this is not sufficient enough to ensure proper management and regulation of the public facility in a legal manner. It aims to promote its relationship with the citizen to develop economic projects. Therefore, the management resorts to hold administrative contracts, but these contracts are not as applicable as private law since they have special system. This paper aims to examine and identify the nature of the administrative contract and to determine the mechanism of contracting it and its characteristics and attempts to differentiate between the administrative contract and other contracts. It is clear that the management contracts have a special nature due to the nature of the contracting parties and the relevance of the contract to the development and economic plans of the state. The special nature of the administrative contracts are not due to the fact that they are contracts of public or private law, however, they derive their specificity from their position in the contract and their relevance to the development of the contracting state. In other words, these contracts don’t only aim at achieving a private interest for the parties, but they also aim at achieving the public interest which at the end rebound to the benefit of the society as a whole